2016
DOI: 10.5307/jbe.2016.41.4.389
|View full text |Cite
|
Sign up to set email alerts
|

Drying Characteristics of Agricultural Products under Different Drying Methods: A Review

Abstract: Purpose: Drying is one of the most widely used methods for preserving agricultural products or food. The main purpose of drying agricultural products is to reduce their water content for minimizing microbial spoilage and deterioration reaction during storage. Methods: Although numerous drying methods are successfully applied to dehydrate various agricultural products with little drying time, the final quality of dried samples in terms of appearance and shape cannot be guaranteed. Therefore, based on published … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 49 publications
0
6
0
Order By: Relevance
“…According to the results obtained, the freeze dried Bintangor orange sample was able to retain the most vitamin C, which was 76%. Lee et al (2016) showed similar results, finding that the freeze dried tomato powder had a higher level of ascorbic acid, around 78.5%, than spray dried and drum dried powder. In their work, the oxidative loss of ascorbic acid during vacuum drying was 31.3%, which was higher than freeze drying (21.5%) and spray drying (25.8%).…”
Section: Antioxidant Properties Of the Powdersmentioning
confidence: 57%
See 1 more Smart Citation
“…According to the results obtained, the freeze dried Bintangor orange sample was able to retain the most vitamin C, which was 76%. Lee et al (2016) showed similar results, finding that the freeze dried tomato powder had a higher level of ascorbic acid, around 78.5%, than spray dried and drum dried powder. In their work, the oxidative loss of ascorbic acid during vacuum drying was 31.3%, which was higher than freeze drying (21.5%) and spray drying (25.8%).…”
Section: Antioxidant Properties Of the Powdersmentioning
confidence: 57%
“…Spray dried powder had the shortest time of wettability. This indicates a good reconstitution of the properties of the powder obtained due to the small size of the beads that were produced by the spray drying apparatus (Lee et al, 2016). Schwartz and Lorenzo (2014) also stated that all dried powder had excellent properties with the powder being higher in carbohydrates than fats and proteins.…”
Section: Degree Of Cakingmentioning
confidence: 93%
“…In addition, lower L * values were observed as a result of HTAD-MW when compared with HTAD. During combined drying of microwave and hot air, orange snacks may get internally carbonized due to extreme heat accumulation [75].…”
Section: Color Propertiesmentioning
confidence: 99%
“…3,8 Freeze dryers inflict the lowest loss to aroma and organic compounds of the dried product ingredients, compared with the fluidized bed and the combined microwave-convective dryers. 9 However, the equipment of freeze drying comes with a high maintenance cost 10 and the energy consumption is approximately twice than the convective drying. 11 Vacuum drying is also reported to have positive effects on quality compared with the hot air convective drying, but the energy consumption is increased at a similar scale.…”
mentioning
confidence: 99%
“…17,18 Due to the high drying efficiency, FBD is well-suited for large scale operations. 19,20 It is also an economical method compared to vacuum, 12,21 hybrid, 3,8,21 freeze 10,11,21 and convective drying. 14,21 Generally, FBDs are more convenient and attractive in industry, even for farmers, to produce high-quality products.…”
mentioning
confidence: 99%